Innovative video capsule endoscopy for detection of ubiquitously elongated small intestinal villi in Cronkhite-Canada syndrome - Heinzow, Hauke Sebastian (Termedia Publishing House, 2013)
Cronkhite-Canada syndrome (CCS) is a rare non-familial disorder with multiple gastrointestinal polyps and ectodermal changes. Adenomatous and carcinomatous changes have been reported. Video capsule endoscopy is a useful non-invasive tool to reveal polypoid lesions of the gastrointestinal tract suspicious for malignancy. We report a case of a patient with CCS with excessively elongated intestinal villi resembling dense sea grass under water as well as multiple polyps of the intestinal mucosa revealed by video capsule endoscopy. This report presents for the first time small bowel video sequences of CCS qualifying video capsule endoscopy for screening purposes and early detection of malignancy.